Peran Guru Dalam Meningkatkan Soft Skill Peserta Didik Melalui Pembelajaran Ppkn Di MTS Negeri 3 Muaro Jambi - Juliani, Anita; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2023)
Abstrak; The purpose of carrying out this research was to find out the teacher's role in improving the soft skills of students at MTsN 3 Muaro Jambi. This research was conducted at MTsN 3 Muaro Jambi from 8 February to 16 April 2022. The method for obtaining data used observation, interview and documentation techniques. The data analysis performed was of a qualitative nature. The results obtained after the implementation of the research, namely the role of PPKn teachers in improving the Soft Skills of students at MTsN 3 Muaro Jambi, were not optimal, this was caused by several factors such as the urgency of implementing learning aimed at hard skills not soft skills, teachers did not really understand about soft skills, teachers do not know and understand various methods and strategies in improving soft skills in learning and have an impact on the monotony of the methods used during the implementation of learning and foster boredom in students, the teacher does not understand the character of students, causing the teacher to find it difficult to manage students and make learning not conducive. The advice given after this research was carried out was that the teacher should further improve his Soft Skills and exemplify students with a good attitude. This is because the teacher is at the forefront of students in finding references to soft skills and good character.